The primary moult of the Brambling Fringilla montifringilla evaluated by four different methods - Holmberg, Thomas (Ornis Svecica, 1992)
The primary moult of the Brambling Fringilla montifringilla was studied between 1988 and 1991 at Ånnsjön (63°15'N; 12°28'E) in the Swedish mountain region. The duration of primary moult was estimated in four different ways: 1) By linear regression of population data; 2) By calculating the mean duration of moult of 34 recaptured birds, assuming a linear relationship between time and moult progression; 3) By using data from the same recaptured birds but correcting for the non-linear progression of moult; 4) By using field data on the rate of shedding of different primaries and the growth rate of individual feathers to construct a moult score versus time curve. Linear regression of population data gave results varying from 32 to 70 days depending on population and method of analysis. The other three methods all resulted in a primary moult duration of 58–60 days. The recaptured birds often showed a weight decrease between captures but this seemed not to affect the moult speed. The mean starting date of moult of the population varied from 8 July to 18 July in the four years. The males tended to start a little earlier than the females, but the difference is not significant. The estimated duration of primary moult (ca 59 days) is considerably longer than the result (46.5 days) of another recently published study. The difference is probably due to different methods of analysis.